Earth Video Cube: A Geospatial Data Cube for Multisource Earth Observation Video Management and Analysis - Zilong Li; Zhipeng Cao; Peng Yue; Chenxiao Zhang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
Earth observation (EO) videos are undergoing rapid expansion due to the swift advancements in aerial, spaceborne, and ground remote sensing technologies enabling the continuous capture of imagery of the Earth's surface. Compared with traditional image-based EO data, EO videos offer persistent EO, rendering a promising observation resource across diverse applications, including climate monitoring and hazard assessment. The continuous observation capability introduces a challenge to the community, i.e., how to effectively manage and fully harness the value of the substantial volume of EO videos. In this article, we propose a novel approach leveraging a spatiotemporal data cube with EO video management to facilitate analysis. It suggests an analysis ready data (ARD) for EO videos, termed as analysis ready video data, which is incorporated into an Earth video cube. The ARD includes semantics at frame, object/trajectory, and event levels. This article presents the cube data organization and query processing for EO videos. A prototype system is implemented to demonstrate the applicability of the approach.